PPAT responsibilities in signing a deed of sale and purchase based on a blank form - Aslan Noor; Barry Irma Perdana; Angelica Riza Claudya; Nurmala Pitaloka; Livia Kris Imani (Jurnal Info Sains : Informatika dan Sains, 2024)
PPAT is a public official who is trusted by the State to make land sale and purchase deeds with the main tasks and obligations delegated through Government Regulation (PP) No. 24 of 2016 concerning Amendments to PP No. 37 of 1998 regarding the Position Regulations for Officials Making Land Deeds. In practice, some PPATs sometimes use blank forms as the basis for making land sale and purchase deeds. This research aims to investigate the responsibilities of Land Deed Drafting Officials (PPAT) in signing sale and purchase deeds based on the use of blank forms. The research method used is normative legal research with a statutory and conceptual approach. The research results show that the responsibility of a Land Deed Drafting Officer (PPAT) in signing a Sale and Purchase Deed based on blank forms has a major impact on legal certainty and protection for the community. PPAT must carry out its duties with full ethics, independence and professionalism, paying attention to the formal and material requirements for making deeds. Violation of these requirements can result in administrative sanctions, dismissal, or even criminal prosecution. The quality of ethics and compliance with statutory regulations are key factors in maintaining the integrity and trust of the public in the role of PPAT in the process of transferring land rights.